1999
DOI: 10.1161/01.hyp.34.4.802
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Nitric Oxide Inhibition and Chronotropic Responses in Rat Isolated Right Atria

Abstract: The long-term administration of nitric oxide synthesis inhibitors induces arterial hypertension accompanied by left ventricular hypertrophy and myocardial ischemic lesions. Because the enhancement of sympathetic drive has been implicated in these phenomena, the current study was performed to determine the potency of beta-adrenoceptor agonists and muscarinic agonists on the spontaneous rate of isolated right atria from rats given long-term treatment with the nitric oxide inhibitor N(omega)-nitro-L-arginine meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Because other authors have shown that the NO system is related to a bradycardic effect (experiments in NOS knockout mice, applications of NO donors and/or NOS inhibitors), 11,22 , our findings can be interpreted, in this context, as suggesting a direct negative chronotropic effect of NO on the pacemaker activity. Our results support the idea that the L-NAME-induced tachycardia observed in in vivo experiments is not caused by direct action of the inhibitor on the showed that L-NAME did not affect the beat rate, 23 whereas others have reported that low doses of an NO donor or 8-bromo-cGMP increase the spontaneous beating rate in atria isolated from guinea-pig and in sinoatrial node cells from rabbit, by activation of the hyperpolarization inward current. 24 Taking our results into consideration, it is probable that other humoral factors may be involved in the L-NAME-induced tachycardia in autonomic-blocked rats.…”
Section: State Of the Artsupporting
confidence: 88%
“…Because other authors have shown that the NO system is related to a bradycardic effect (experiments in NOS knockout mice, applications of NO donors and/or NOS inhibitors), 11,22 , our findings can be interpreted, in this context, as suggesting a direct negative chronotropic effect of NO on the pacemaker activity. Our results support the idea that the L-NAME-induced tachycardia observed in in vivo experiments is not caused by direct action of the inhibitor on the showed that L-NAME did not affect the beat rate, 23 whereas others have reported that low doses of an NO donor or 8-bromo-cGMP increase the spontaneous beating rate in atria isolated from guinea-pig and in sinoatrial node cells from rabbit, by activation of the hyperpolarization inward current. 24 Taking our results into consideration, it is probable that other humoral factors may be involved in the L-NAME-induced tachycardia in autonomic-blocked rats.…”
Section: State Of the Artsupporting
confidence: 88%
“…Age‐matched control rats received tap water alone. Systolic blood pressure was measured by using a modified tail‐cuff method in conscious animals ( Riado et al , 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…The L-NAME-induced tachycardia observed in in vivo experiments may not be due to a direct action of the inhibitor on the pacemaker. In isolated right atria, Riado et al (27) showed that L-NAME did not affect the beat rate, whereas others have reported that low doses of an NO donor or 8-bromo-cGMP increase the spontaneous beating of isolated guinea pig atria and rabbit sinoatrial node cells by activation of the hyperpolarization inward current (28,29). In addition, NO can elicit either positive or negative inotropic effects (30,31).…”
Section: Time (Min)mentioning
confidence: 99%